2013
DOI: 10.1590/s1413-35552012005000113
|View full text |Cite
|
Sign up to set email alerts
|

Gross Motor Function Classification System Expanded & Revised (GMFCS E & R): reliability between therapists and parents in Brazil

Abstract: | Background: Several studies have demonstrated the importance of using the Gross Motor Function Classification System (GMFCS) to classify gross motor function in children with cerebral palsy, but the reliability of the expanded and revised version has not been examined in Brazil (GMFCS E & R). Objective: To determine the intraand inter-rater reliability of the Portuguese-Brazil version of the GMFCS E & R applied by therapists and compare to classification provided by parents of children with cerebral palsy. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
20

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 17 publications
2
25
0
20
Order By: Relevance
“…The results of this study indicated almost perfect agreement between physical and occupational therapists with more than 5 years of experience in neurology (Group 1), in which they classified the motor level of children using the Brazilian version of the GMFCS E & R. Results similar to this were obtained only in the Brazilian study developed by Silva et al 19 (K=0.90), in which direct observation was held and the parents were questioned about methods of mobility for the motor level classification, involving one undergraduate student of OT and one occupational therapist with nine years of experience.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The results of this study indicated almost perfect agreement between physical and occupational therapists with more than 5 years of experience in neurology (Group 1), in which they classified the motor level of children using the Brazilian version of the GMFCS E & R. Results similar to this were obtained only in the Brazilian study developed by Silva et al 19 (K=0.90), in which direct observation was held and the parents were questioned about methods of mobility for the motor level classification, involving one undergraduate student of OT and one occupational therapist with nine years of experience.…”
Section: Discussionsupporting
confidence: 67%
“…Morris and Bartlett 18 mention that the use of videos of GMFCS allows students to understand that cerebral palsy comprises more than one motor type or topographical distribution, and show that a child with quadriplegia (bilateral spastic CP) can be classified into different levels of GMFCS (II, III, IV or V) 18 . Although the GMFCS and the GMFCS E&R consist in classifications of easy application, studies that assess their reliability in Brazil are scarce 5,19 and did not verify their validity with other health professionals with different levels of experience in the area (strata) 20 , including undergraduate students, who are involved in the treatment of children with cerebral palsy. The aim of this study was to evaluate the reliability of the Portuguese version (Brazil) of the GMFCS E&R for students and health professionals (physical and occupational therapists), with different levels of experience.…”
Section: Introductionmentioning
confidence: 99%
“…Morris, Galuppi, and Rosenbaum 45 claim that the caregivers tend to functionally classify their children as more limited, however, they know the functional performance of the child in more varied situations than the health professionals, who have contact with children in specially designed clinical environments enabling better functional ability, with fewer barriers, something that emphasizes the importance of the caregivers' participation and vision in the rehabilitation process of their children. 45,46 This suggests the need for therapeutic planning to include the guidance and awareness of parents as to the real ability of their children so that they can actively participate in their activities of daily living. 47 In domain N -social participation, a significant difference was found between the groups that corroborates with Palisano 48 who says that the participation of young people with Cerebral Palsy is influenced by many factors such as their personal characteristics and their relatives and that the greater their impairment, the greater the restriction on participation.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] GMFCS scoring system was developed by Palsino and colleagues in 1997, later revised and expanded in 2007 to overcome its limitations. [4,9] GMFCS classifies CP into five levels; I, II, III, IV and V. The scores are ordinal and in the direction I (good) → V (bad) i.e. opposite to the direction of NFS which runs in direction 1 (bad) → 5 (good).…”
Section: Discussionmentioning
confidence: 99%